The Effect of Sales Influence Tactic (Sit) In Forming Consumer Alternative Evaluation - Arie Indra Gunawan; Fatya Alty Amalia; Rialdy Trike (Jurnal Sekretaris dan Administrasi Bisnis, 2021)
Salespeople through personal selling activities provide a very dominant role for the industry, their level of effectiveness in making sales has an impact on company performance, so it is not uncommon for sales people to carry out aggressive sales strategies (Sales Influence Tactics) which tend to be pushy. Meanwhile, consumers currently can make their own choices through alternative evaluation activities that they do, consumers do not like it when in alternative evaluation activities they experience a pressure on information given by force, consumers will be more resistant. This study aims to determine the effect of sales influence tactics and determine what factors are of concern to consumers in personal selling sales influence tactics activities. The study was conducted on 204 consumers who have interacted with sales people at the store point, the analysis was carried out using SEM-PLS to measure the research model and produce interpretations. The research findings show that not all aspects of sales influence tactics have a positive effect, there are only two aspects that give influence and become the attention of consumers, namely information exchange and ingratiation aspects. This study provides input to increase the effectiveness of sales people in conducting personal selling.